Black Coaches' Roles in the Holistic Development of Student-Athletes - Singer, John N.; Armstrong, Ketra L. (My University, 2001)
This study examined Black coaches' (n=123) roles in the holistic development of student-athletes, and barriers impeding the coaches' contributions. The data were obtained by surveying Black coaches in attendance at a national Black coaches convention. The results revealed differences based on coaches' personal and team demographics. The findings indicated that: (a) coaches generally agreed with their responsibilities regarding assisting student-athletes with personal problems and academics, yet were in less agreement concerning offering spiritual guidance and monitoring student-athletes' friends and social support groups; (b) Black student-athletes' experiences were less favorable than others; and (c) time constraints, institutional barriers, and coaching demands were the most prevalent barriers coaches face(regarding their contributions to student-athlete development). MANOVA were performed to examine differences in the responses based on the coaches' demographics (i.e., whether a head or assistant coach) and team demographics (i.e., the race and gender composition of teams coached). The suggestions offered by the coaches focused on: (a) the encouragement of more interaction between student-athletes and coaches, (b) greater attention to life skills issues, (c) collaborations with community and campus entities, and (d) better student-athlete support programs. Assistant coaches usually serve as liaisons between athletes and head coaches, and therefore athlete development may be inherent in the job responsibilities of their respective positions. Coaches believed that student-athletes in general are having "good" sport experiences, however, they believed that Black-student-athletes' experiences are less favorable than the experiences of most athletes in general. Responsibilities coaches were generally in strongest agreement with were: assisting athletes with their personal problems, taking an active role in study table and athlete's academic progress, and encouraging athletes to confide in them. The results of this study revealed that Black coaches perceived the overall experiences of Black student-athletes to be less satisfying than those of all student-athletes (male, female, Black, White, etc.). Thus, addressing the holistic development of Black student-athletes begins with recognizing the manner in which their cuItured (racial/ethnic) identity influences their development process.
Keywords: coaches; race; demographics